Persuasive Strategies in Pakistani Public Health Broadcasts: A Systemic Functional Multimodal Analysis - Zameer, Nazia; Fatima, Arooj; Nawaz, Muhammad Shafqat (Pakistan Languages and Humanities Review, 2025)
This study investigates the diverse persuasive strategies in Pakistani COVID-19 public service announcements (PSAs). Adopting a Systemic Functional Multi-modal Analysis framework, it deconstructs three distinct broadcasts from the National Command and Operation Center (NCOC), Inter-Services Public Relations (ISPR), and SAMAA TV. The analysis reveals three "persuasive profiles": The NCOC uses authoritative instruction with high-modality language to establish logical necessity. ISPR uses moral and nationalistic unity, presenting the pandemic as a war to appeal to common values. SAMAA TV uses persuasion by juxtaposition, employing a neutral, fact-based tone to lead audiences to infer a cause-and-effect account. The results show how ideational, interpersonal, and textual decisions construct customized messages that capture distinct institutional objectives. This research offers a detailed, linguistically grounded model for analyzing persuasive discourse in public health crises.